Changes in Active Commuting to School in Czech Adolescents in Different Types of Built Environment across a 10-Year Period - Dygrýn, Jan; Mitáš, Josef; Gába, Aleš; Rubín, Lukáš; Frömel, Karel (International journal of environmental research and public health, 2015)
Active commuting (AC) to school represents a great opportunity to incorporate walking or cycling into adolescents' everyday routine. The objective of the study was to describe changes in AC in Czech adolescents across a 10-year period in different built environments. Data from the 2001 and 2011 Czech Census of Population and Housing were used to examine the mode of transportation taken to school in 6236 adolescents. Changes in AC over time were analyzed for low and high walkable areas separately in two Czech regional cities, Olomouc and Hradec Králové. Between 2001 and 2011, the proportion of adolescents actively commuting to school decreased by 47%, from an absolute rate of 49.1% to 26%. The proportion of active commuters fell in low walkable areas by 61% and in high walkable areas by 39%. The results indicated that adolescents in 2011 were 2.7 times less (OR = 0.365, p < 0.001) likely to actively commute than in 2001. The AC behavior in Czech adolescents has a negative tendency to replicate travel-to-school patterns in adolescents previously described in more developed countries. The findings might serve as a recommendation for municipal policy.
Keywords: Students; Female; charakteristiky bydlení; dítě; ženské pohlaví; Adolescent Behavior; Transportation; Adolescent; lidé; Environment Design; školy; Schools; Residence Characteristics; cyklistika; doprava; Male; Czech Republic; mladiství; Walking; životní prostředí - projekt; Česká republika; Child; studenti; mužské pohlaví; chování mladistvých; chůze; Bicycling; Humans